Gestational diabetes mellitus complicated with depression in pregnant women: a biopsychosocial analysis and intervention strategies - Yan Wang; Yunxia Quan (BMC Pregnancy and Childbirth)
Abstract Objective To investigate the incidence and influencing factors of comorbid depression in pregnant women with gestational diabetes mellitus (GDM), analyze their interaction effects, and propose targeted intervention strategies. Methods A retrospective analysis was conducted on clinical data from 746 pregnant women who underwent regular prenatal examinations at our hospital from March 2022 to March 2024. All participants were screened for GDM using the oral glucose tolerance test (OGTT) at 24–28 weeks of gestation. Based on GDM diagnosis, the cohort was divided into GDM and non-GDM groups, with demographic and clinical indicators compared between groups. For GDM patients, the Hamilton Depression Rating Scale-17 (HAMD-17) was used to assess depressive symptoms, categorizing them into a negative screened group (HAMD-17 score > 7) and a positive screened group (HAMD-17 score ≤ 7). Univariable analysis was performed to identify potential influencing factors, followed by multivariable logistic regression to determine independent associated factors and interaction effects. Results Among 746 participants, 84 were diagnosed with GDM (incidence: 11.26%). Univariable analysis revealed that GDM was significantly associated with advanced maternal age (≥ 35 years), pre-pregnancy overweight/obesity (BMI ≥ 24 kg/m²), adverse pregnancy history, family history of diabetes, polycystic ovary syndrome (PCOS), poor dietary habits, insufficient physical activity, poor sleep quality, and elevated serum estradiol (E2), progesterone (P), and cortisol (Cor) levels (P < 0.05). Multivariable logistic regression confirmed these factors as independent associated factors for GDM (P < 0.05). Among the 84 GDM patients, 27 (32.14%) had comorbid depression. Univariable analysis identified adverse pregnancy history, elevated E2/P/Cor levels, personal/family history of depression, unintended pregnancy, poor glycemic control, GDM-related complications, and low social support (SSRS score < 33) as potential associated factors for depression (P < 0.05). Multivariable analysis further demonstrated that adverse pregnancy history, elevated E2/P/Cor levels, prior depression history, poor glycemic control, and low social support were independent associated factors for comorbid depression (P < 0.05). Interaction analysis using Jvenn ( https://jvenn.toulouse.inrae.fr/app/example.html ) revealed that adverse pregnancy history and elevated E2/P/Cor levels were shared influencing factors for both GDM and comorbid depression. Conclusions (1) Advanced maternal age, pre-pregnancy overweight/obesity, adverse pregnancy history, diabetes family history, PCOS, poor lifestyle habits, and elevated E2/P/Cor levels are independent associated factors for GDM. (2) Adverse pregnancy history, elevated E2/P/Cor levels, prior depression history, poor glycemic control, and low social support are independent associated factors for comorbid depression in GDM patients. (3) Adverse pregnancy history and elevated E2/P/Cor levels represent shared interaction factors influencing both conditions.